2023
DOI: 10.1002/aenm.202203892
|View full text |Cite
|
Sign up to set email alerts
|

Designing Bidirectionally Functional Polymer Electrolytes for Stable Solid Lithium Metal Batteries

Abstract: The development of high energy density lithium metal batteries has been retarded by the uncontrolled lithium dendrite formation and unstable Ni‐rich cathode–electrolyte interface (CEI). Herein, the bidirectionally functional polymer electrolytes (BDFPE) are designed via direct UV solidification of functional polymer species on electrode surfaces to simultaneously handle the interface issues faced by anodes and cathodes. By constructing the BDFPE, a smooth and dendrite‐free lithium deposition is enabled for Li|… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 47 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…The more intimate contact between the PVH-5 electrolyte and Li metal anode can contribute to achieving the uniform deposition of Li-ions and mitigates the growth of lithium dendrites. 29 Besides, the effect of HFA additive on the electrochemical stability of SSEs was also investigated by linear sweep voltammetry (LSV) measurement in Li‖SSEs‖SS cells (Fig. 1f).…”
Section: Resultsmentioning
confidence: 99%
“…The more intimate contact between the PVH-5 electrolyte and Li metal anode can contribute to achieving the uniform deposition of Li-ions and mitigates the growth of lithium dendrites. 29 Besides, the effect of HFA additive on the electrochemical stability of SSEs was also investigated by linear sweep voltammetry (LSV) measurement in Li‖SSEs‖SS cells (Fig. 1f).…”
Section: Resultsmentioning
confidence: 99%
“…Li//BDFPE//NMC622 demonstrates the formation of stable CEI and F‐enriched SEI with favorable features for interfacial protection. [ 350 ]…”
Section: Anode Interface Chemistrymentioning
confidence: 99%
“…Li//BDFPE//NMC622 demonstrates the formation of stable CEI and F-enriched SEI with favorable features for interfacial protection. [350] Li metal deposits under PVDF-PEO/LiTFSI (FPEO) with/without dual-salt of Al/Li have been reported (Figure 13). [351] Li metal for single Li-salt displays dendrites with rough (voids/cracks) topography, whereas dual-salts have smooth dendrites-free Li deposits.…”
Section: Li-metal Batteries (Lmbs)mentioning
confidence: 99%
“…Tremendous efforts have been made to restrain the adverse reactions on the Li-metal anode, such as fabrication of favorable host structures, regulation of electrolyte compositions, modification of separator, and so on. Among them, electrolyte engineering to promote the in-situ formation of a stabilized SEI is one of the plausible solutions. Alternatively, the construction of an artificial SEI could be another simple approach. , As a class of porous coordination polymers, metal–organic frameworks (MOFs) have attracted increasing attention in the electrochemical community due to their large surface area, highly ordered structure, and well-developed porosity. For example, Avery et al have demonstrated that MOFs can be used as a cathode additive to mitigate polysulfide shuttle effect in lithium–sulfur (Li–S) batteries for a better cycling performance .…”
Section: Introductionmentioning
confidence: 99%